The Antibiofilm Efficacy of Gold Nanoparticles Against Acinetobacter baumannii: none - Al-Shaabani, Mahmood Jasim Mohammed; Turki, Ahmed Mohammed; Al-Mathkhury, Harith J. Fahad (Iraqi Journal of Science, 2020)
Acinetobacter baumannii is highly adapted to hospital environments, causing persistent chronic infections due to its ability to form biofilms. In this work, the antibiofilm activity of AuNPs with a subMIC concentration of 9.34 μg/ml was investigated by the microtiter plate method against 80 clinical isolates of A. baumannii. The results revealed that the biofilm was significantly (P< 0.05) reduced by 48.2 – 82.1%.